Rozwój i funkcjonowanie przedsiębiorstw spedycyjnych w Polsce - Dyczkowska, Joanna (Progress and Functioning of Forwarders in Poland, 2005)
Forwarders, which work on European and Polish market are a net organization. A tendency to firms joinings and their diverse creations, offering a full range of services is an attempt of adaptation of these firms to new circumstances on an international market The range of logistic services introduced to given customers depend on their requirements, and these depends on sizes of their needs. The examples - ELDA and PTC from Middle Pomerania show us the economics result by co-operation with forwarders. Forwarding firms working on the Polish market are multi-company and net organisations, which co-operate with each other to reach a common target - possibly the highest level of customer satisfaction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 214-223